OP0201 Outcome of Lupus Nephritis: Results from an International, Prospective, Inception Cohort Study. (10th June 2014) - Hanly, J.G.; O'Keeffe, A.G.; Urowitz, M.B.
Abstract : Background: The outcome of lupus nephritis has evolved over the past decade due to improved immunosuppressive therapies and close attention to co-morbidities. Objectives: To study a large, prospective, multi-ethnic/racial, inception cohort of patients with systemic lupus erythematosus (SLE) to determine the outcome of lupus nephritis with current standard of care. Methods: An international research network of 37 investigators in 32 academic centers from 11 countries participated in this study. Patients who fulfilled the American College of Rheumatology (ACR) classification criteria for SLE were evaluated within 15 months of diagnosis of SLE and annually thereafter, using a standardized protocol. Data collection included patient demographics, ACR classification criteria, medications, International Society of Nephrology (ISN) classification of chronic kidney disease (CKD) and of renal biopsies (when performed), estimated glomerular filtration rate (eGFR) and proteinuria (ePrU), end stage renal disease (ESRD), SLE disease activity index-2000 (SLEDAI-2K) and Systemic Lupus International Collaborating Clinics (SLICC)/ACR damage index (SDI). Chi-squared test and t-tests were used for group comparisons and Kaplan-Meier curves were produced for time to event analyses. Results: There were 1, 827 SLE patients, 89% females with a mean ±SD age of 35.1±13.3 years. The ethnic/racial distribution was 49.2% Caucasian, 16.6% African, 15.4% Hispanic, 14.9% Asian and 3.9% other. At enrollment, SLE duration was 0.5±0.3 years, SLEDAI-2K was 5.4±5.4, SDI was 0.31±0.74. The duration of follow-up was 4.6±3.4 years. Lupus nephritis, as defined in the ACR classification criteria, occurred in 499 (27.3%) patients at enrollment and in an additional 202 (11.1%) during follow-up for a cumulative prevalence of 38.4%. The frequency of nephritis was more common in Africans (46%), Hispanics (55%) and Asians (44%) compared to Caucasians (26%) (p<0.001). Renal biopsies from 312 (44.5%) patients revealed the following ISN classes (%): I (0.4), II (10.4), III (23.3), IV (37.8), V (28.1) and VI (0). At presentation, impaired renal function (eGFR ≤60 ml/min) was present in 13.8% of patients with nephritis, and proteinuria (ePrU ≥0.25 gr/day) occurred in 58.2%. Patients with nephritis were treated with corticosteroids (89.7%), antimalarials (64.9%) and immunosuppressive (cyclophosphamide, azathioprine, mycophenolate mofetil) drugs (81.5%). At final follow-up 16.7% of patients with nephritis had impaired renal function and 36.7% had proteinuria. Using the ISN classification of CKD, the proportion of patients with stage 5 CKD (renal failure; GFR ≤15 ml/min) was 1.6% at enrollment and 3.8% at final followup. The Kaplan-Meier estimated proportion of patients developing ESRD (as defined by the SDI) after 10 years was 4.5% for the entire cohort, 7.8% for patients with lupus nephritis and 0.8% for patients without lupus nephritis. Conclusions: Lupus nephritis occurred in 38% of SLE patients in a large multi-ethnic/racial inception cohort. Nephritis presented most frequently around the time of diagnosis of SLE and was associated with individual patient's racial/ethnic background. Although the outcome with standard of care was generally favourable, the results indicate the need for further therapeutic advances in the care of patients with lupus nephritis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1113